ANALISA DAN EVALUASI PROTOTYPE PENGINTEGRASIAN DATA P4GN MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING BADAN NARKOTIKA NASIONAL PROVINSI ACEH - Munawir Munawir; Zulfan Zulfan; Susmanto Susmanto; Taufik Hidayat (Universitas Serambi Mekkah, 2019)
With the rapid development of technology and the ease of obtaining information and communication, so that the impact on the use of information technology is misused, in order to improve the performance of institutions one way to determine the form of information systems that can meet business needs and in line with the organization's business development is develop an enterprise architecture. Enteprise architecture describes a process for organizing and directing information systems development plans, which consist of data architecture, application architecture and technology architecture to obtain support and commitment from management in implementing integrated information system development. The methodology used in making enterprise architecture models here is Enterprise Architecture Planning (EAP). In EAP, architecture describes the data, applications and technology needed to support an organization's business. This research is used as a case study is the National Narcotics Agency of Aceh province. Enterprise data architecture is one product towards the planning stage of enterprise architecture. Data architecture describes a variety of key data, called entities, that are used in a business environment. Application architecture describes the applications needed to support business functions and organize information in a business environment. The technology architecture defines the main technologies needed to provide an environment for applications that manage data. This research, explains the application of Enterprise Architecture Planning (EAP) on developing prototype of integrating P4GN data in the National Narcotics Agency of Aceh Province. The business modeling stage is the process of defining the business of an organization that explains the organization's business functions. The results of business modeling are used as a basis for defining data architecture, application architecture and technology architecture. The results of business modeling which are the main functions of the National Narcotics Agency of the Province of Aceh are the prevention function, the function of community empowerment and the eradication function. Data architecture produced 22 data entity candidates and their relationships. In the application architecture obtained 31 application candidates. Whereas technology architecture shows 7 business locations spread across 23 Aceh provinces. The networks used are intranet and internet.